The Effects of national fundamental factors on regional house prices: A factor-augmented VAR analysis - Xiang Gao; Wen Kong; Zhijun Hu (Journal of Risk and Financial Management, 2022)
Using panel data from 30 regions in China during the period 1999:01-2020:12, this paper evaluates the effects of national fundamentals affecting the movement of regional house prices by estimating a factor-augmented VAR model. We construct and examine a hypothesis that national fundamentals affecting regional house prices, such as monetary policy (short-term interest rate and M2), real output, and inflation rate, may affect regional house prices through their impacts on common factors. The empirical results show that monetary shocks (both interest rate and M2) can significantly affect regional house prices, but the effects are pretty different across regions. However, the effects of the real output and inflation rate are less important. Therefore, this study offers valuable information for regulators to improve the effectiveness of monetary policy to stabilize house markets from a regional perspective.
Keywords: 650; factor-augmented VAR model; monetary policy; national fundamental factors; regional house price